Suicide rates in Iceland in 2000-2019 : a nationwide population-based study - Bergþóra Kristín Ingvarsdóttir 1989- (2021)
Worldwide suicides are a serious public health concern. Alarmingly, recent research suggests an increase in suicides among certain groups. The aim of this population-based study was to examine change in overall suicide rates and by established demographic and clinical risk factors (i.e., sex, age, relationship status, residency, history of severe self-harm) in Iceland through the years 2000-2019. Toward this end, data on all registered suicides in Iceland in 2000-2019 were obtained from death certificates (ICD-10 diagnostic codes X60-84). Information on sex, age, relationship status, residency at the time of death and history of selfharm (ICD-10 diagnostic codes: X60-84, Y87.0 and Y10-34) warranting inpatient care or emergency room (ER) visit was obtained from the Icelandic Hospital Registries. Poisson regression analyses were used to determine change in suicide rates over time. No changes in overall suicide rates or suicide rates by sex, age, relationship status, or residency or those who self-harmed warranting an ER visit were observed across time (p-value > 0.05). There was however a decrease in suicide rates among those admitted to inpatient care due to selfharmed, with rates decreasing from 22,363 to 8,564 individuals per 100,000 individuals that were hospitalized due to self-harm from 2000 to 2019 (IRR=0.383, 95% CI: 0.265 – 0.553). The findings indicate that suicide rates in Iceland have remained stable over the past twenty years. There was also evidence that prevention efforts targeting individuals hospitalized due to self-harm have been effective in decreasing suicides in this high-risk group. Keywords: Suicides, self-harm, population-based, suicide attempts